2019
DOI: 10.1038/s41598-018-36420-1
|View full text |Cite
|
Sign up to set email alerts
|

A near infrared light emitting electrochemical cell with a 2.3 V turn-on voltage

Abstract: We report on an organic electroluminescent device with simplified geometry and emission in the red to near infrared (NIR) spectral region which, has the lowest turn-on voltage value, 2.3 V, among light emitting electrochemical cells (LEECs). We have synthesized and characterized three novel ruthenium π-extended phenanthroimidazoles which differ on their N^N ligands. The use of dimethyl electron donating groups along with the π-extended phenanthroimidazole moiety promotes ambipolar transport thereby avoiding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Bideh et al. reported efficient NIR LECs based on a binuclear ruthenium phenanthroimidazole complex (complex 34 , Figure 3) in 2017 [54] . In comparison to the complex reported in an earlier study, [45] dinuclear ruthenium complex 34 showed a red‐shift of ca.…”
Section: Materials For Long‐wavelength Lecsmentioning
confidence: 83%
See 1 more Smart Citation
“…Bideh et al. reported efficient NIR LECs based on a binuclear ruthenium phenanthroimidazole complex (complex 34 , Figure 3) in 2017 [54] . In comparison to the complex reported in an earlier study, [45] dinuclear ruthenium complex 34 showed a red‐shift of ca.…”
Section: Materials For Long‐wavelength Lecsmentioning
confidence: 83%
“…In 2019, Bideh et al proposed novel ruthenium complexes with πextended phenanthroimidazoles which differ on their N^N ligands. [47] The use of dimethyl electron donating groups along with the π-extended phenanthroimidazole moiety promotes ambipolar transport. The LECs employing complexes 21 and 22 (Figure 2) showed deep-red EL emission peaks at 664 and 695 nm, respectively.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Performance of LECs can also be improved by providing more balanced charge transportation within the emissive layer. This parameter was examined with a series of three complexes Ru-16-Ru-18 where an ambipolar charge transportation ability was provided by attaching a phenanthroimidazole ligand [108]. As an interesting point and in addition to the improvement of the charge transportation, use of an ancillary ligand with extended aromaticity both contribute to reducing the HOMO-LUMO gap and red-shift the PL emission.…”
Section: Metal Complexes Using Nir Emittersmentioning
confidence: 99%
“…The first iTMC-based LEC, fabricated in 1996 by Lee et al, showed that Ru­(II) polypyridine complexes exhibit favorable electroluminescence (EL) and thermal stability properties . Much research on Ru­(II) complexes has been done in the past decade to increase the efficiency of LECs. To date, [Ru­(bpy) 3 ] +2 and its similar complexes have been used in most studies due to their high metal-to-ligand charge transfer (MLCT), long half-time of the excited state, and high EQE in solution and at room temperature …”
Section: Introductionmentioning
confidence: 99%